2015
DOI: 10.1111/jpi.12261
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: HDAC1 inhibition by melatonin leads to suppression of lung adenocarcinoma cells via induction of oxidative stress and activation of apoptotic pathways

Abstract: Melatonin is an indoleamine synthesized in the pineal gland that shows a wide range of physiological and pharmacological functions, including anticancer effects. In this study, we investigated the effect of melatonin on drug-induced cellular apoptosis against the cultured human lung adenocarcinoma cells and explored the role of histone deacetylase (HDAC) signaling in this process. The results showed that melatonin treatment led to a dose- and time-dependent decrease in the viability of human A549 and PC9 lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 58 publications
1
57
0
1
Order By: Relevance
“…18 We used SPSS 19.0 software to perform the statistical analysis in this study. Student unpaired t tests (between 2 groups) and 1-way ANOVA (for >2 groups) followed by Bonferroni (equal variances assumed) or Tamhane T2 (equal variances not assumed) were used where applicable.…”
Section: Discussionmentioning
confidence: 99%
“…18 We used SPSS 19.0 software to perform the statistical analysis in this study. Student unpaired t tests (between 2 groups) and 1-way ANOVA (for >2 groups) followed by Bonferroni (equal variances assumed) or Tamhane T2 (equal variances not assumed) were used where applicable.…”
Section: Discussionmentioning
confidence: 99%
“…As a potent free radical scavenger and antioxidant, melatonin has the capacity to scavenge up to 10 reactive oxygen species (ROS) via the cascade reaction means, which distinguishes melatonin from the classic antioxidants that scavenge only one or less ROS [1113]. Additionally, numerous publications have reported that melatonin inhibits the growth of a variety of cancers: lung [5, 14, 15], breast [1620], prostate [2124], liver [25, 26], colon [27, 28], etc. The oncostatic mechanisms of melatonin are related to several hallmarks of cancer, including anti-proliferation [14], induction of apoptosis [5, 14, 15], inhibition of invasion and metastasis [29, 30], anti-angiogenesis [16, 31], and enhancement of immunomodulation [32] among others.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC1s are frequently overexpressed in various types of human cancer, melatonin treatment decreasing expression of HDAC1 [64]. Fan et al reported that melatonin acts as a suppressor in colorectal cancer cells and osteosarcoma cells via HDAC signaling inhibition.…”
Section: Regulation Of Histone Deacetylases (Hdacs)mentioning
confidence: 99%
“…Fan et al reported that melatonin acts as a suppressor in colorectal cancer cells and osteosarcoma cells via HDAC signaling inhibition. On the other hand, HDAC1 inhibitors induce ROS production, so oxidative stress might be an important mechanism by which melatonin induces cancer cell death [64].…”
Section: Regulation Of Histone Deacetylases (Hdacs)mentioning
confidence: 99%